Emotional flow monitoring for health using FLOWSENSE: an experimental study to test the impact of antismoking campaigns - Reis, E.; Arriaga, P.; Postolache, O. (5th IEEE International Conference on E-Health and Bioengineering, EHB 2015, 2016)
A multi-sensory system, entitled FLOWSENSE, was developed to monitor emotional responses in real time using both subjective (self-report) and objective (physiological) measures. To evaluate the program's reliability, an experiment was conducted using antismoking campaigns. Participants (N=92) were exposed to three advertisements of humor or of fear-appeals and asked to report continuously the emotions and the intensity they were feeling. Physiological responses were also collected by the system. Results showed statistically robust differences of emotions reported between the two different types of ads. Those exposed to the fear appeals ads reported significantly more often, with higher intensity and for longer periods of time fear and sadness, while the humor ads induced stronger positive emotions of happiness. The system was also able to localize fine grains of information which can help researchers understand and identify how health campaigns are influencing emotions and how this information may contribute to wider health outcomes.